An Unusual Case of Bleeding in Small Intestine - Vujasinovic, Miroslav; Måhl, Martin; Burgos, Carmen Mesas; Zetterström, Cecilia K.; Nastic, Denis; Johansson, Gabriele Wurm; Toth, Ervin (Turkish Journal of Gastroenterology, 2021)
Cite this article as: Vujasinovic M, Mahl M, Mesas Burgos C, et al. An unusual case of bleeding in small intestine. Turk J Gastroenterol. 2021; 32(7): 608-610.